Efektivitas Online Library Services di Era New Normal: Studi Pada UPT Perpustakaan Universitas Lampung - Purnamayanti, Arnila; Windah, Andi; Putra, Purwanto; Sugiyanta, Sugiyanta (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
(Objectives) This research examines the Effectiveness of Online Library Services in the New Normal Era. As we all know, it has been almost two years since the world has experienced a COVID-19 pandemic.This also has an impact on library institutions, where the library is the parent of the School/University Institution itself. With these conditions, like it or not, libraries are also required to continue to provide excellent service even in the current state of the COVID-19 pandemic in order to continue to support an optimal learning process. The UPT Library of the University of Lampung is under the auspices of the University of Lampung, currently the UPT of the library is trying to adapt to the "New Normal" situation where it continues to provide online library services to users.  (Method) This research used kuantitative descriptive survey method (Findings) The results of the study found that the Online Library Services UPT Lampung University Library was effective for the category of program success, the success of the intended goals, and input for achieving overall goals. However, for the category of satisfaction with the output level program, it is still quite effective, this is because there is still quite a long time needed to access e-resources services and verify scientific papers that are perceived by users. In this case, the UPT of the University of Lampung library can make improvements and updates to the online services provided so that the level of satisfaction with the program can be effective.